Identification of Ferns in the Suranadi Nature Tourism Park Area, West Lombok Regency in 2023 - Reni Anggraini; Ahmad Raksun; I Gde Mertha (Jurnal Biologi Tropis, 2023)
This research aims to determine the species of ferns (Pteridophytes) and to determine the relationship patterns of ferns (Pteridophytes) in the Suranadi Natural Tourism Park Area, West Lombok Regency. The research was conducted from June to July 2023. This type of research is descriptive research using the roaming method, with a roaming area of 52 Ha. The samples of this research were ferns (Pteridophytes) found at the research location. Data collection techniques are carried out by means of observation, identification and documentation. The results of the research show that in the Suranadi Nature Tourism Park there are 3 orders, 10 families, 16 genera and 33 species of ferns. The fern grouping pattern is depicted in the form of a dendogram, the dendogram was created using the NTSYS application. In this study, the closest level of relationship is species Christella parasitica with species Christella subpubescens namely 94%. Meanwhile, the ferns with the furthest degree of relationship are the species of the family Polypodiaceae and species of the family Thelypteridaceae, with a kinship level of 50%.